EVALUATION OF PHYSIOTHERAPY SERVICES PROVIDED TO CHILDREN INSPECIAL EDUCATION CENTERSIN THE CITY OF NAJRANFROM THE PARENTS' PERSPECTIVE - MansourHamadAliAlFadhil, HadiSaeedHadiAlAlhareth, Hamad Hadi Saleh Al yami, AmeenSalehAliAlZamanan, KhaledAlihadiAlalhareth, (Chelonian Research Foundation, 2023)
Physiotherapy is one of the basic supportive health professions that contribute to the prevention and treatment of physical disability, growth disorders, movement functions and improving the quality of life. Physiotherapists achieve these goals through an advanced understanding of the basics of body movement and how it works, by diagnosing the symptoms of disease and injury, and then using several treatment methods for patients, such as physical therapy with exercises, thermal, water, electrical, light, manual and respiratory therapy, and other conditions for which physical therapy is an integral part of the integrated treatment plan (Pountney,2007). Physical therapy aims to treat people with motor disabilities by developing their motor abilities through preventive, therapeutic, and rehabilitative programs to facilitate their integration and participation in the daily life of society.